2010
DOI: 10.1097/bpo.0b013e3181c6318c
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Juvenile Osteochondritis Dissecans Lesions of the Knee Using Poly 96L/4D-lactide Copolymer Bioabsorbable Implants

Abstract: Poly 96L/4D-lactide copolymer bioabsorable implants seem to be safe and effective for the management of unstable juvenile OCD lesions of the knee. They offer stability for the healing OCD lesions, with minimal reaction from degradation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…Compiled with other published data, a complication rate of 23% makes screw breakage the leading complication. 8,14 We hypothesized that differential decomposition is a major factor in screw breakage. It is biologically plausible that the intraosseous part of a bioabsorbable screw decomposes much more quickly because of better circulation and higher exposure to resorptive cells and chemicals when compared with the head of the screw located within the cartilage or the joint cavity itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compiled with other published data, a complication rate of 23% makes screw breakage the leading complication. 8,14 We hypothesized that differential decomposition is a major factor in screw breakage. It is biologically plausible that the intraosseous part of a bioabsorbable screw decomposes much more quickly because of better circulation and higher exposure to resorptive cells and chemicals when compared with the head of the screw located within the cartilage or the joint cavity itself.…”
Section: Discussionmentioning
confidence: 99%
“…The recent literature has shown excellent clinical and radiologic results after such treatment for OCD. 3,6,[8][9][10][11][12] However, prior research has also elucidated a certain risk profile for such implants, such as reduced biomechanical properties compared with metallic screws and local inflammation due to glycolic and lactic acid, leading to effusion and synovitis, as well as the considerably higher cost. [12][13][14] Of particular interest, however, is mechanical implant failure.…”
mentioning
confidence: 97%
“…Two authors have reported healing rates (seven of seven and seven of eight) and no major complications [44,61]. Furthermore, authors have demonstrated no adverse reactions resulting from the degradation of modern implants [76]. However, these implants are not without their complications: breakage with loose body formation, opposing cartilage damage, and possible cyst formation and synovitis [22].…”
Section: Treatmentmentioning
confidence: 99%
“…The main advantages of bioabsorbable fixation are the lack of metal artifact on postoperative MRI as well as theoretically no subsequent surgery needed for implant removal [66]. Bioabsorbable implants can fail though due to screw breakage, screw back out, reactive synovitis, and loss of compressive force over time [70][71][72][73].…”
Section: Lesion Fixationmentioning
confidence: 99%
“…Bioabsorbable screws, pins, tacks, and darts have been designed and utilized with overall good results [66][67][68][69]. The main advantages of bioabsorbable fixation are the lack of metal artifact on postoperative MRI as well as theoretically no subsequent surgery needed for implant removal [66].…”
Section: Lesion Fixationmentioning
confidence: 99%